Developing Low-Cost LoRaWAN Internet of Things Devices for Water Resources Monitoring in Bali - Radek, Oborny; Michiel, Steltman; Ni Nyoman, Pujianiki; Ngakan Ketut, Acwin Dwijendra; Oka, Widyantara (INTI International University, 2024)
In this study, we developed a solar-powered prototype using an ESP-32 MCU, commercially available sensors, and a LoRaWan communication module. The components cost less than $30 USD. The prototype has been running on solar power for two months in room conditions, repeating the sleep-wake cycle and transmitting sensor data - temperature, battery %, light color, and accelerometric data - every ten minutes over LoRaWAN to a cloud data storage. While the data only reflect room settings, and not real environmental data, the operating record demonstrates steady behavior, power autonomy, and data transfer, which is a necessity for IoT devices that monitor water supplies in the field. In the future, the developed devices will be used in Bali,Indonesia, to monitor the hydrological status during an impending water crisis.